2019
DOI: 10.9734/ijbcrr/2019/v27i130113
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition, Nutritional Values and Antibacterial Activities of Watermelon Seed (Citrullus lanatus)

Abstract: The World Health Organization (WHO) defines traditional medicine as the sum total of the knowledge, skills, and practices based on the theories, beliefs and experiences indigenous to different cultures, whether explicable or not, used in the maintenance of health as well as in the prevention, diagnosis, improvement or treatment of physical and mental illness. Plants are traditionally used for treatment of bacterial infections. The aim of this study was to investigate chemical composition, nutritional evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…The seed was observed in this review to enjoy the highest attention on antimicrobial activity with dif f erent claims such as Babaiwa et al, (2017) emphasizing the use of the ethyl acetate extract of CL seeds to treat a wild range of bacterial due to the presence of so me chemical compounds such as f atty acids, hexamethyl-2-ethyl acridine, gamma-tocopherol and methyl phthalate. The aqueous and methanolic extract of CL seed powder had been shown to have good antimicrobial properties (Sola et al, 2019). The antimicrobial ef f icacy of methanolic extract of CL seed was reported by Sathya and Shoba (2014).…”
Section: Antimicrobialmentioning
confidence: 90%
“…The seed was observed in this review to enjoy the highest attention on antimicrobial activity with dif f erent claims such as Babaiwa et al, (2017) emphasizing the use of the ethyl acetate extract of CL seeds to treat a wild range of bacterial due to the presence of so me chemical compounds such as f atty acids, hexamethyl-2-ethyl acridine, gamma-tocopherol and methyl phthalate. The aqueous and methanolic extract of CL seed powder had been shown to have good antimicrobial properties (Sola et al, 2019). The antimicrobial ef f icacy of methanolic extract of CL seed was reported by Sathya and Shoba (2014).…”
Section: Antimicrobialmentioning
confidence: 90%
“…Consequently, the observed antibacterial properties of extracted melanin from C. lanatus seeds indicate its potential therapeutic efficacy in the traditional medicinal use of this plant in treating bacterial ailments such as diarrhea, gastrointestinal infections, respiratory disorders, and dermatological conditions. Sola et al [108] examined the chemical composition, nutritional assessment, and antibacterial properties of C. lanatus seeds. Watermelon seed powder was subjected to maceration with methanol at a 4:1 liquid-to-solid ratio for 24 h at RT.…”
Section: Seedsmentioning
confidence: 99%
“…Due to the existence of many nutritious benefits, watermelon seeds have applications in a variety of culinary products. Sola et al found that watermelon seed extracts contain antimicrobial capabilities [99]. Furthermore, roasted watermelon seeds are used by customers as an appetite stimulant and to alleviate constipation [83].…”
Section: Nutritional Composition Bioactives' Content and Associated H...mentioning
confidence: 99%